THE IMPLEMENTATION OF TBLT PROCEDURE AT THE FIRST GRADE OF TOURISM DEPARTMENT - Fransiska Gustiana; Veni Roza; Merry Prima Dewi (ANGLO-SAXON: Jurnal Ilmiah Program Studi Pendidikan Bahasa Inggris, 2020)
The purpose of the research is to find out the Implementation of Task Based Language Teaching Procedure at the First Grade of Tourism Department in SMKN 2 Bukittinggi. This research was descriptive qualitative. The data were obtained through observation and interview. The observation was conducted in four meetings and informants of this research were the teacher who taught at the First Grade of Tourism Departments and some student. The data were analyzed by using flow model of Miles and Huberman in Sugiono. The finding reveals that Task Based Language Teaching Procedure in generally had implements by the teacher with process pre task, task, planning, report, analysis, and practice but the teacher did not apply yet all of Process. The teacher did not implement one of activities from task process that was walk around to monitor and to encourage students to communicate in the target language because in the class the teacher prefer walked around to monitor whether the students did the task or not. For the other process had implements by the teacher but not always implemented in every meeting depend on the topic of the learning.